Curcumin-containing chitosan nanoparticles as a potential mucoadhesive delivery system to the colon. (June 2013) - Chuah, Lay Hong; Billa, Nashiru; Roberts, Clive J.; Burley, Jonathan C.; Manickam, Sivakumar
<x xml:space="preserve">Abstract</x> In the present study, we investigate the mucoadhesive characteristics and release of the anticancer agent curcumin, contained in chitosan nanoparticles (CS-NPs). Such a system has potential therapeutic benefits in the treatment of colon cancer through prolonged retention and delivery. The CS-NPs were ionically gelled with tripolyphosphate (TPP) and registered an isoelectric pH of 6.2 (z-average diameter of 214 nm ± 1.0 nm). pH variations around the isoelectric point caused a reduction in CS-NPs electrical charge which correspondingly increased the z-average due to agglomeration. Curcumin release from CS-NPs was slowest at chitosan to TPP weight ratio of 3:1, with a significant retention (36%) at the end of 6 h. Adsorption isotherms of mucin on CS-NPs fitted both the Freundlich and Langmuir models, suggesting a monolayer-limited adsorption on heterogeneous sites with varied affinities. Encapsulated curcumin exerted an influence on the adsorption of mucin due to H-bonding as well as π-π interactions between the phenolic moieties of curcumin and mucin.